A new correlation to determine the Lockhart-Martinelli parameter from vertical differential pressure for horizontal venturi tube over-reading correction. (December 2022) - Chen, Yuan; Chinello, Gabriele; Tait, Paul; Jia, Jiabin
Abstract: Venturi tubes are widely used to measure the gas flow rate in a wet-gas stream. To calculate the gas flow rate, wet-gas Venturi tubes require the liquid loading (i.e. Lockhart-Martinelli parameter) to be known as an input to a so-called over-reading correction correlation. It is challenging to derive the Lockhart-Martinelli parameter without installing additional devices in series to the Venturi tube thus adding significant cost and complexity. A relatively low cost and easy to implement method is to derive the Lockhart-Martinelli parameter by measuring the pressure drop across the Venturi tube or along a pipe section. A correlation that predicts the Lockhart-Martinelli parameter by measuring the pressure drop along a vertical pipe section downstream of the Venturi tube is presented. The correlation was obtained by fitting experimental results from TUV-SUD National Engineering Laboratory's wet-gas test facility with nitrogen-water in a 4″ vertical pipe, Lockhart-Martinelli from 0.04 to 0.29, and gas Froude number from 1 to 2.7. Further experiments were conducted at Spirax Sarco Engineering plc to evaluate the performance of the proposed correlation under steam-water conditions. Tests were conducted with steam-water in a vertical 2″ pipe, Lockhart-Martinelli from 0.005 to 0.064, and gas Froude number from 0.55 to 1.35. The Lockhart-Martinelli parameter is predicted within ±0.035 absolute value with the proposed new correlation for both the National Engineering Laboratory and Spirax Sarco datasets. Gas flow rate values within approximately ±5% error are obtained with the proposed correlation together with ISO/TR 11583 over-reading correlation for the NEL dataset. Although further improvements to the proposed method are required, this work demonstrates the efficacy of an agile, simple, and low-cost differential pressure method to aid the Venturi meter to determine the gas mass flow rate in wet-gas flow. Highlights: A new correlation is developed to determine the LM parameter in wet-gas flow. Venturi gas mass flow rate over-reading is corrected within ±5% relative error. The correlation is validated on steam-water flow at Spirax Sarco facility.